2003
DOI: 10.1021/la020971n
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of N2 and CO2 on Zeolite X Exchanged with Potassium, Barium, or Lanthanum

Abstract: The zeolite X ion exchanged with K, Ba, or La was tested for the adsorption of N2 and CO2. The physical adsorption of N2 at 77 K confirmed that the zeolite framework remained intact after exchange and thermal treatment. The isotopic transient analysis of N2 adsorbed on the samples at 303−333 K indicated that BaX had the highest uptake of N2, with a heat of adsorption equal to 4.5 kcal mol-1. In addition, the vibrational frequency of adsorbed N2 was most perturbed by the presence of Ba cations. Results from Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…This phenomenon might be caused by a decrease of partial negative charge of oxygen atoms adjacent to Ba 2+ cations. In this matter, an analysis of the CO 2 adsorption on zeolites KX, BaX and LaX has effectively indicated that the zeolite KX was the most basic among these three zeolites [28]. In contrast, a study of CO 2 adsorption on the clinoptilolite has indicated that the substitution of Na + and K + by Ca 2+ caused a rise of the basicity of the framework oxygen acting as basic center [7].…”
Section: Influence Of the Structural Characteristics Of Zeolites On Tmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon might be caused by a decrease of partial negative charge of oxygen atoms adjacent to Ba 2+ cations. In this matter, an analysis of the CO 2 adsorption on zeolites KX, BaX and LaX has effectively indicated that the zeolite KX was the most basic among these three zeolites [28]. In contrast, a study of CO 2 adsorption on the clinoptilolite has indicated that the substitution of Na + and K + by Ca 2+ caused a rise of the basicity of the framework oxygen acting as basic center [7].…”
Section: Influence Of the Structural Characteristics Of Zeolites On Tmentioning
confidence: 99%
“…The molecules that have a great permanent quadrupole moment might interact strongly with the gradient of the electric field induced by the zeolites cations [50]. The quadrupole moment of certain gas varies as following: CO 2 > CO > N 2 > H 2 > CH 4 ≈ Ar ≈ Kr [28]. Goj et al [51] have effectively showed that the zeolites ITQ-3 and ITQ-7 adsorb preferentially the CO 2 to detriment of N 2 .…”
Section: Influence Of Adsorbates Characteristics 221 Influence Of Tmentioning
confidence: 99%
“…Also, the charge density of divalent cations is higher than that of monovalent cations. 21 Therefore, the amount of CO 2 adsorbed on calcium-impregnated sorbent would be expected to be quite high.…”
Section: Fa-raw A-raw A-k A-limentioning
confidence: 99%
“…In both processes, the role of the compensation cation can be crucial. In the past few years, some experimental studies [44][45][46][47][48] have been dealt with the influence of either the nature or distribution and density of these extra-framework cations on the adsorption properties of various zeolite systems. It was clearly established that these cations play a key role in the adsorption phenomena in such materials.…”
Section: Adsorption Microcalorimetry At 302 K: Role Of Compensation Cmentioning
confidence: 99%